FRI0574 CLINICAL RESPONSE TO HIGH-DOSE INTRAVENOUS METHYLPREDNISOLONE IN CHILDHOOD AUTOIMMUNE UVEITIS: A RETROSPECTIVE ANALYSIS. (June 2019) - Schnabel, Anja; Unger, Elisabeth; Bruck, Normi; Holl-Wieden, Annette; Morbach, Henner; Berner, Reinhard; Leszczynska, Anna; Hedrich, Christian
Abstract : Background: Intraocular inflammation accounts for up to 10-15% of total blindness cases [1]. The incidence of uveitis in children ranges around 4.9/100.000, and a significant number of patients develop chronic courses and irreparable complications [2]. An impressive 74% of children with juvenile idiopathic arthritis (JIA)-associated uveitis are legally blind at diagnosis [3]. This underscores the importance of timely diagnosis and effective anti-inflammatory treatment. Objectives: To evaluate the clinical response to high-dose intravenous methylprednisolone (IVMP) in children and adolescents with autoimmune uveitis. Methods: A retrospective chart review was conducted in two tertiary referral centers in Germany (TU Dresden and University of Würzburg) to investigate treatment responses to IVMP (10-30mg/kg/day on three successive days with a total of one to five IVMP at monthly intervals) in children and adolescents (<16 years) with autoimmune uveitis diagnosed between 2003 and 2016. Clinical features of uveitis, disease activity, outcomes, and concomitant anti-inflammatory treatment were documented at treatment initiation, after 3 and 6 months. Results: Fifty-six patients (93 affected eyes) with a median age of 7.4 (range: 2.5-16.7) years were included. In 29% of patients uveitis was associated with JIA. Uveitis was predominately located in the anterior segment (43%), bilateral (66%) and recurrent (43%). Complications occurred in 77% of patients and included visual loss, synechiae, cataract and/or retinal lesions. Patients with active uveitis received between 1 and 5 IVMP. Visual acuity improved significantly (0.52±0.33 to 0.69±0.30 at 3 months (p<0.001), 0.78±0.31 at 6 months (p<0.001)) independent of the number of IVMP. Furthermore, anterior chamber cells (45% to 18%, p=0.01), synechiae (47% to 32%, p<0.005), keratic precipitates (27% to 18%, p<0.001), papillary edema (30% to 13%, p<0.001) and/or macular edema (15% to 4%, p=0.01) improved 3 months after IVMP. Over all, children treated with 3 or more IVMP (n=27) (as compared to 1 IVMP (n=18)) experienced fewer relapses (Median 1 [0-6] vs 3 [0-13], p=0.186), developed fewer cataracts (7% vs 39%, p<0.02) and less frequently required treatment with biologics (19% vs 39%, p=0.174). Conclusion: High-dose IVMP induces rapid improvement in children with autoimmune uveitis. Data suggest improved outcomes in children treated with three or more courses of IVMP when compared to one course (without reaching statistical significance). Prospective randomized trials in larger cohorts are required to confirm results. References: [1] Nussenblatt RB. The natural course of uveitis. Int Ophthalmol. 1990; 141:303–8. [2] [2] Päivönsalo-Hietanen T et al. Uveitis in children: population-based study in [3] Finland. Acta Ophthalmol Scand. 2000; 78(1):84-8. [4] [3] Woreta F at el. Risk factors for ocular complications and poor visual acuity at presentation among patients with uveitis associated with juvenile idiopathic arthritis (JIA). Am JOphthalmol 2007; 143:647–55. Disclosure of Interests: Anja Schnabel: None declared, Elisabeth Unger: None declared, Normi Bruck: None declared, Annette Holl-Wieden: None declared, Henner Morbach: None declared, Reinhard Berner Grant/research support from: Local Principal Investigator in a Clinical Trial on Canakimumab for sJIA supported by Novartis (Trial Registration: NCT00886769, NCT00889863, NCT00426218 and NCT00891046 ) Local Principal Investigator in a Clinical Trial DAP-PEDOST-11-03 supported by Merck (Trial Registration EUDRACT 2013-000864-28), Anna Leszczynska: None declared, Christian Hedrich Grant/research support from: Novartis Pharmaceuticas for Research study on effector T cells in psoriasis, Speakers bureau: In 2016: Roche Pharmaceuticals, RheumatoLogisch, Dresden, Germany; Novartis, Advisory board > Travel costs.